2018
DOI: 10.1016/j.ctro.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The EMBRACE II study: The outcome and prospect of two decades of evolution within the GEC-ESTRO GYN working group and the EMBRACE studies

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
492
8
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 496 publications
(521 citation statements)
references
References 86 publications
12
492
8
9
Order By: Relevance
“…Two patients had limited under-dosage after re-planning with 37.8 and 39.1 Gy to CTV-T LR, respectively, and marginally insufficient dose to CTV-T HR (42.5 Gy) in one patient. Furthermore it was found, that it [14][15][16][17][18][19][20] was the "large" rectal fillings assessed by the RTTs, that were most often associated with lack of target coverage during treatment (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two patients had limited under-dosage after re-planning with 37.8 and 39.1 Gy to CTV-T LR, respectively, and marginally insufficient dose to CTV-T HR (42.5 Gy) in one patient. Furthermore it was found, that it [14][15][16][17][18][19][20] was the "large" rectal fillings assessed by the RTTs, that were most often associated with lack of target coverage during treatment (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…All measurements are visually assessed. [14][15][16][17][18][19][20] be that the macroscopic tumour occupies only a small fraction of the entire target volume irradiated to 45 Gy [30]. Therefore, the organ motion (and in particular systematic relocation of organs) is by far the most challenging aspect in EBRT for LACC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the high-risk group (stage III or IVA, any stage and positive nodes) (p = 0.022), there were increased distant metastases (DMs) with a decreasing number of CTx cycles (fewer than five cycles). Early analysis from image-guided intensity-modulated external beam radio-CTx and MRI-based adaptive BT in a locally advanced cervical cancer (EMBRACE) I trial also showed higher DMs in node-positive and advancedstage patients who received fewer than five cycles of CTx [24].…”
Section: Delivery Of Chemotherapy To Enhance Treatment Results In Laccmentioning
confidence: 99%
“…The EMBRACE II study report was released in 2018 and reviewed the outcome and prospect of two decades of evolution within the GEC-ESTRO GYN working group and EMBRACE studies [24]. The EMBRACE II was initiated in April 2016 (https://www.embracestudy.dk) and defines interventions that address local, nodal, and systemic treatment as well as OAR exposure.…”
Section: Bt Is Mandatory Unless There Are Technical Problemsmentioning
confidence: 99%